Association of Hyperuricemia with Chronic Low Back Pain (KYAMC Journal, 2022)
Background: The Back pain affects about 20% of the population in Bangladesh in each year between the ages of 30-60 years. A well-defined pathology is identified in only about 15% of patients.Objective: To identify the association of hyperuricemia in patients with chronic low back pain.Materials and Methods: A descriptive cross-sectional study was performed on 180 patients among the ages of 18 to 75 years with chronic low back pain (CLBP). Data was collected through a structured questionnaire. X-rays and Magnetic Resonance Imaging (MRI) of the lumbosacral spine had been used to evaluate any findings in terms of low back pain. Serum uric acid (sUA) levels had been tested and recorded.Results: Joint pain (p < 0.001), lumbar disc prolapse (p = 0.023), and disc degeneration (p = 0.011) were more in High-sUA than Low-sUA group. Female patients in H-sUA group had significantly higher occurrence of joint pain(p = 0.002), lumbar disc prolapse (p = 0.019), and disc degeneration (p = 0.004) than L-sUA group. In regression analysis, female sex (p = 0.036), duration of CLBP (p = 0.031), and sUA level (p = 0.025) were associated with radiological findings. In female patients association of duration of CLBP (p = 0.046) and sUA (p = 0.009).Conclusion: The serum UA level was significantly associated with CLBP in female patients. More studies are warranted to explore whether the two conditions exist simultaneously or there is a direct causal relationship between the conditions.KYAMC Journal. 2022;12(04): 213-217